2018
DOI: 10.1016/j.biortech.2017.10.099
|View full text |Cite
|
Sign up to set email alerts
|

Secondary effluent purification by a large-scale multi-stage surface-flow constructed wetland: A case study in northern China

Abstract: Assessment of treatment performance in the large-scale constructed wetland (CW) for secondary effluent purification remains limited. The aim of this case study was to therefore to investigate the long-term treatment capacity of organics and ammonium pollutants in a large-scale multi-stage surface-flow (SF) CW fed with secondary effluents from the wastewater treatment plants (WWTPs) in northern China. The results for two-and-half-year study period indicated that the water quality parameters including chemical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…CWs rely on the simultaneous occurrence of several complicated physical, chemical, and biological processes for removing pollutants, including sorption and sedimentation, photolysis, hydrolysis, volatilization, plant uptake and accumulation, plant exudation, and microbial degradation [6,8,9]. Wu, et al [10] conducted long-term monitoring of secondary effluent treatment from wastewater treatment plants by a continuous large-scale constructed wetland system. The average removal efficiency of COD and NH 4 + -N reached 53% and 72%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…CWs rely on the simultaneous occurrence of several complicated physical, chemical, and biological processes for removing pollutants, including sorption and sedimentation, photolysis, hydrolysis, volatilization, plant uptake and accumulation, plant exudation, and microbial degradation [6,8,9]. Wu, et al [10] conducted long-term monitoring of secondary effluent treatment from wastewater treatment plants by a continuous large-scale constructed wetland system. The average removal efficiency of COD and NH 4 + -N reached 53% and 72%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Constructed wetlands (CWs) are a well-known and widely recognized solution, due to their good operation performance [1,2], cost-effectiveness [3], and ability to withstand impact loads [4][5][6][7]. This technology is capable of treating various types of wastewater, including agricultural wastewater, industrial effluent, polluted river water, and domestic sewage [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the operational effectiveness of tail-water CWs had observed a steady increase in conjunction with the rise in their application cases. It has been found that CWs exhibited high removal efficiencies for ammonia nitrogen (NH 4 + -N), chemical oxygen demand (COD) and total phosphorus (TP) [4,14]. Wu et al conducted an extensive followup study for two and a half years on the tail-water from a wastewater treatment plant that was treated by a large-scale vertical-flow CW [4].…”
Section: Introductionmentioning
confidence: 99%
“…Influent water stabilization to wastewater treatment systems (WWTSs) in terms of pollutant concentration and composition has been widely implemented as a strategy to stabilize the effluent water quality and realize sustainable operation [1,2]. Currently, the resilience of a WWTS as well as the response of a WWTS to dramatic influent variations has drawn increasing attention in both academia and industry, because of the rapid socioeconomic development and global climatic change [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite high construction and maintenance costs, buffering facilities such as automated control and storm tanks are still the most common measures to increase WWTS resilience [4]. In a simulated biofilm reactor (SBR), there generally exists a notable linear correlation between the influent and effluent water quality levels, and thus influent stabilization is an important condition for achieving water quality discharge standards [1,5]. Therefore, in large-scale integrated BR systems for wastewater treatment, stabilization, detention or aeration ponds are designed as the front end of sequential facilities to buffer any possible shock loads in terms of the quantity or composition [1,3,6].…”
Section: Introductionmentioning
confidence: 99%